Ovarian tissue cryopreservation for fertility preservation in 418 girls and adolescents up to 15 years of age facing highly gonadotoxic treatment. Twenty years of experience at a single center - Poirot, Catherine; Brugieres, Laurence; Yakouben, Karima; Prades‐Borio, Marie; Marzouk, Flora; Lambert, Guenolee; Pacquement, Helene; Bernaudin, Francoise; Neven, Benedicte; Paye‐Jaouen, Annabel; Pondarre, Corinne; Dhedin, Nathalie; et al. (Acta obstetricia et gynecologica Scandinavica, 2019)
Introduction The preservation of fertility is an integral part of care of children requiring gonadotoxic treatments for cancer or non‐malignant diseases. In France, the cryopreservation of ovarian tissue has been considered and has been offered as a clinical treatment since its inception. The aim of this study is to review 20 years of activity in fertility preservation by ovarian tissue cryopreservation (OTC) for children and the feasibility of oocyte isolation and cryopreservation from the ovarian tissue at a single center. Material and methods Retrospective study including patients aged 15 years or younger who underwent OTC, combined for some with oocyte cryopreservation of isolated oocytes, before a highly gonadotoxic treatment for malignant or non‐malignant disease was initiated. We describe the evolution of activities in our program for fertility preservation and patient characteristics at the time of OTC and follow up. Results From April 1998 to December 2018, 418 girls and adolescents younger than 15 years of age underwent OTC, representing 40.5% of all females who have had ovarian tissue cryopreserved at our center. In all, 313 patients had malignant diseases and 105 had benign conditions. Between November 2009 and July 2013, oocytes were isolated and also cryopreserved in 50 cases. The mean age of patients was 6.9 years (range 0.3‐15). The most frequent diagnoses in this cohort included neuroblastoma, acute leukemia and hemoglobinopathies; neuroblastoma being the most common diagnosis in very young patients. During follow up, three patients requested the use of their cryopreserved ovarian tissue. All had undergone ovarian tissue transplantation, one for puberty induction and the two others for restoring fertility. So far, no pregnancies have been achieved. Eighty‐four patients who had OTC died. Conclusions Ovarian tissue cryopreservation is the only available technique for preserving fertility of girls. To our knowledge this is the largest series of girls and adolescents younger than 15 years so far reported on procedures of OTC before highly gonadotoxic treatment in a single center.